The Storage Building for Agricultural Product - Atmodjo M C T (International Conference on Engineering and Technology Development (ICETD), 2017)
The Agricultural product is necessary special treatment in order to long life availibility. The building as the storage for agricultural product should design unique which we call as SILO and it means that the quality of the product should better and longlife. In agriculture, postharvest handling is the stage of crop production immediately following harvest, including cooling, cleaning, sorting and packing. The instant a crop is removed from the ground, or separated from its parent plant, it begins to deteriorate. Postharvest treatment largely determines final quality, whether a crop is sold for fresh consumption, or used as an ingredient in a processed food product